Feasibility in the use of the UV-Visible region for the characterization of glucose in deionized water using Arduino 1 - Sanchez-Monroy, Virginia; Barros-Martinez, Luis Enrique; Hidalgo-Pedraza, Alejandro; Mendoza-Munguia, Braulio Adriel; Sanchez-Brito, Miguel (Revista Mexicana de Ingenieria Biomedica, 2023)
With an estimated approximately 2 million deaths per year, diabetes is one of the top 5 deadliest noncommunicable diseases globally. Although this disease is not fatal, the degradation of the patient’s health due to a bad plan to control their glucose levels can have a fatal outcome. In order to lay the foundations for the development of a device that allows estimating glucose levels in some body fluid, we present the results obtained not only for the estimation of glucose in deionized water, but also describe the development and configuration of the created device. After analyzing 50 signals obtained from 5 different glucose concentrations, the feasibility of using the developed device for the analysis is evident, since, considering the K-Nearest Neighbors (KNN) algorithm, all the signals were associated correctly to the glucose group to which they belong.